Establishing Link And Match Programs To Increase Graduates’ Competencies Of Vocational High School Center Of Excellent (Journal of Namibian Studies : History Politics Culture, 2023)
The Indonesian goverrnment has managed to increase the rate of graduate absorption in industries through the implementation of the link and match programs which fostered a collaboration between Vocational High School Center of Excellence (VHS-CS) and its industrial partners. The aim of this research is to unveil the strategies adopted in the link and match program of VHS-CS in its effort to improve the absorption rate of its graduates in indutries relevant to their competencies. This is a multi-case study with the qualitative approach. The research involved 24 informants from three VHS-CS in Malang Regency, East Java, Indonesia. The data collected were then analyzed by applying interactive and comparative techniques of multi-site data analysis. The research found that the strategies adopted in the link and match programs consitute one of the central government’s 8+i program, which began with the VHS’s planning the curriculum in collaboration with its industry partners. The program was periodically monitored by the team formed by the VHS and the associate team from higher educational institutions chosen by the Ministry of education. Eventually this strategy helped VHS develop the competencies of their graduates in accordance with the demand of stakeholders, and the continuity of program.